Aspergillus niger enhances oxalate production as a response to phosphate deficiency induced by aluminium(III) - Polák, Filip; Urík, Martin; Bujdoš, Marek; Matúš, Peter (Journal of inorganic biochemistry, 2020)
This paper investigates Aspergillus niger's behaviour in the presence of mobile Al3+ species by evaluating the changes in oxalate exudation at various aluminium contents. When the fungus was exposed to Al3+, no significant changes in oxalate production were observed until 100 mg.L-1 aluminium was reached resulting in oxalate production decrease by 18.2%. By stripping the culture medium completely of phosphate, even more prominent decrease by 34.8% and 67.1% at 10 and 100 mg.L-1 aluminium was observed, respectively, indicating the phosphate's significance instead of Al3+ in oxalate production. Our results suggest that the low phosphate bioavailability, which most likely resulted from its interaction with Al3+, stimulated the overproduction of oxalate by A. niger. Furthermore, when the fungus was incubated in aluminium-free media supplemented with 0.1 mM of phosphate, oxalate production increased up to 281.5 μmol.g-1, while at 1.85 mM of available phosphate only 80.7 μmol.g-1 of oxalate was produced. This indicates that oxalic acid is produced by fungus not as a mean to detoxify aluminium, but as an attempt to gain access to additional phosphate.
Keywords: Aspergillus niger; koncentrace vodíkových iontů; hliník; Culture Media; oxaláty; Hydrogen-Ion Concentration; Aluminum; Phosphates; Oxalates; kultivační média; fosfáty